Find the following convolution. Properly scale result. y(t) = sinc(t) * [cos(pi/4 t] + cos (4 pi/4 t)]; sinc(2 pi f_0 t) = sin (2 pi f_0 t)/(2 pi f_0 t)

7 - Find the following convolution. Properly scale result. y(t) = sinc(t) * [cos(pi/4 t] + cos (4 pi/4 t)]; sinc(2 pi f_0 t) = sin (2 pi f_0 t)/(2 pi f_0 t)

This content is for Premium members only.
sign up for premium and access unlimited solutions for a month at just 5$(not renewed automatically)


images - Find the following convolution. Properly scale result. y(t) = sinc(t) * [cos(pi/4 t] + cos (4 pi/4 t)]; sinc(2 pi f_0 t) = sin (2 pi f_0 t)/(2 pi f_0 t)

already a member please login